2021
DOI: 10.3390/ijms22168779
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Mediates the Degradation of Plant ESCRT Component FREE1 in Response to Iron Deficiency

Abstract: Multivesicular body (MVB)-mediated endosomal sorting and macroautophagy are the main pathways mediating the transport of cellular components to the vacuole and are essential for maintaining cellular homeostasis. The interplay of these two pathways remains poorly understood in plants. In this study, we show that FYVE DOMAIN PROTEIN REQUIRED FOR ENDOSOMAL SORTING 1 (FREE1), which was previously identified as a plant-specific component of the endosomal sorting complex required for transport (ESCRT), essential for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Transcript levels of several ATG genes and autophagic flux were induced by iron deficiency in Arabidopsis . The resulting increased autophagic activity under low iron conditions resulted in an increased turnover of a negative regulator of iron absorption and improved plant growth under low iron conditions compared with atg mutants [30]. When zinc is in excess, causing an iron deficiency, iron ions can be remobilized from protein‐bound iron through selective autophagy.…”
Section: Autophagy and Micronutrients—less Abundant But Of Great Impo...mentioning
confidence: 99%
See 1 more Smart Citation
“…Transcript levels of several ATG genes and autophagic flux were induced by iron deficiency in Arabidopsis . The resulting increased autophagic activity under low iron conditions resulted in an increased turnover of a negative regulator of iron absorption and improved plant growth under low iron conditions compared with atg mutants [30]. When zinc is in excess, causing an iron deficiency, iron ions can be remobilized from protein‐bound iron through selective autophagy.…”
Section: Autophagy and Micronutrients—less Abundant But Of Great Impo...mentioning
confidence: 99%
“…Autophagy is induced upon a range of nutrient starvation conditions, highlighting the beneficial role of the process in nutrient acquisition and recycling for basic plant cell function. At the same time, defects in autophagy result in decelerated growth and render the plant inadaptable to changing metabolic status and long-lasting nutrient shortages [19,[26][27][28][29][30].…”
mentioning
confidence: 99%
“…Nevertheless, how FREE1 exports from the nucleus after the termination of ABA signalling and whether a protein dephosphorylation mechanism is involved in FREE1 nuclear export remain unknown. Besides phosphorylation, recent findings have demonstrated that ubiquitination, as well as proteasomal and autophagic degradation pathways, are engaged in the regulation of FREE1 turnover, thereby relieving the inhibitory effect of FREE1 on ABA signalling and metal absorption in plants (Xia et al, 2020; Xiao et al, 2020; Zhang et al, 2021). Since multiple phosphorylations and ubiquitination sites have been identified in FREE1 by mass spectrometry (H. Li et al, 2019; Van Leene et al, 2019), identification of the upstream factors involved in those posttranslational modifications would be crucial for a comprehensive understanding of FREE1‐related regulatory networks in plant growth and stress responses.…”
Section: Introductionmentioning
confidence: 99%
“…In eukaryotes, autophagy is a highly conserved catabolic process that delivers cargos into lysosome (in mammals) or vacuole (in yeast and plant) for degradation. As one of the survival pathways and quality control mechanisms, autophagy plays a wide range of physiological roles in plant growth and development [1][2][3], leaf senescence [4][5][6], plant immunity [7][8][9] and response to environmental stresses [10][11][12][13][14][15]. Based on the morphological and mechanistic characteristics, autophagy can be categorized into three distinct types: macroautophagy, microautophagy and chaperone-mediated autophagy.…”
Section: Introductionmentioning
confidence: 99%